Anti-corrosion material for cement paste, carbon dioxide corrosion resistant cement paste and preparation method and application of carbon dioxide corrosion resistant cement paste
By using activated carbon, nano silica and nano alumina anticorrosion materials in cement slurry, a dense protective film is formed, which solves the problems of compressive strength attenuation and increased permeability of cement stone in CO2 corrosion environment, and realizes cement Long-term effective sealing of rings and efficient CO2 sealing.
Patent Information
- Application Number
- CN202310740303.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-21
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2043-06-21
AI Technical Summary
In the CO2 corrosion environment, cement stone cannot be continuously anti-corrosion after being invaded by corrosive media, resulting in attenuation of compressive strength and increased permeability, and it is impossible to ensure the cementing quality of CCUS wells and long-term effective sealing.
Using anti-corrosion materials including activated carbon, nanosilicon dioxide and nanoalumina, through the combination of mixture A and mixture B, a dense protective film is formed, slowly releasing nanoparticles to fill the holes and continue the reaction, preventing acid gas from entering cement stone, Achieve lasting corrosion resistance.
Under the corrosion conditions of CO2 geological sealing wells, cement stone has high compressive strength, low permeability and good mechanical properties, and has a wide temperature range, ensuring long-term effective sealing of cement rings and achieving efficient CO2 sealing.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cement slurry for cementing oil and gas wells, and in particular to an anti-corrosion material for cement slurry, carbon dioxide corrosion resistant cement slurry, and a preparation method and application thereof. Background Art
[0002] Carbon capture, utilization and storage (CCUS) is currently the only feasible technology that can significantly reduce CO2 emissions. The integrity of the cement sheath is a key technology that determines whether the CO2 geological storage project can be successfully implemented and ultimately achieve long-term storage. As we all know, CO2 exists in the state of supercritical CO2 underground, with characteristics such as low viscosity and strong permeability. At the same time, the silicate cement system is strongly alkaline and CO2 is an acidic gas. Under the long-term erosion of CO2, the cement sheath is very likely to be over-carbonated and decalcified, causing changes in composition, strength attenuation, and increased porosity and permeability, resulting in the destruction of the overall structure of the cement sheath, endangering the long-term effective sealing of the wellbore.
[0003] At present, in order to solve the problem of acidic gases such as CO2 corroding cement rings, anti-corrosion cement slurry systems are widely used at home and abroad. Oil well cement CO2 anti-corrosion materials mainly use ultra-fine inert materials and active siliceous materials, such as the addition of inert ultra-fine barite and other materials by Sinopec Dezhou Research Institute and Li Guanying of National Cheng Kung University by adding fly ash, silica powder and other active materials, through the physical close stacking effect to reduce the permeability of cement stone and react with cement minerals to reduce the alkalinity of cement stone to improve the CO2 corrosion resistance of cement stone. This method only weakens the exchange source of dissolved ions and tries to slow down the penetration rate of CO2 corrosive media. Once the corrosive media enters the interior of the cement stone, it will continue to damage the gel structure of the cement stone and cannot continue to play its anti-corrosion role. Therefore, the anti-corrosion effect is not very ideal.
[0004] CN114133172A discloses a carbon dioxide corrosion resistant cement slurry in cementing and a preparation method thereof. The invention adopts silicate cement, nano-silicon dioxide, UF cellulose fiber, a fluid loss reducer and a dispersant to obtain a CO2 corrosion resistant cement slurry. The nano-silicon dioxide fills and plugs the micropores inside the cement stone, participates in the hydration reaction to increase the Si / Ca of the hydration product, and improves the corrosion resistance of the hydration product. The UF cellulose improves the mechanical properties of the cement stone. However, the applicable temperature range is not given. The temperature in the embodiment is 60°C, the applicable temperature range is small, and the system adaptability is insufficient.
[0005] Therefore, it is urgent to develop a cement slurry with good anti-corrosion ability in a CO2 corrosive environment to ensure the cementing quality of CCUS wells and achieve efficient CO2 storage. Summary of the invention
[0006] The purpose of the present invention is to overcome the problem that cement stone cannot be continuously protected against corrosion after being invaded by CO2 corrosive medium in the prior art, and to provide an anti-corrosion material for cement slurry, carbon dioxide corrosion resistant cement slurry, and a preparation method and application thereof. The carbon dioxide corrosion resistant cement slurry prepared by the anti-corrosion material of the present invention has the characteristics of high compressive strength, low permeability, good sedimentation stability, good rheology, and a wide applicable temperature range after corrosion under the corrosion conditions of CO2 geological storage wells, thereby ensuring long-term effective sealing of CO2 geological storage wells.
[0007] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides an anti-corrosion material for cement slurry, wherein the anti-corrosion material comprises a mixture A and a mixture B; wherein the mixture A comprises activated carbon, nano-silicon dioxide and nano-alumina; the mixture B comprises component C and component D; the component C is selected from diatomaceous earth and / or fly ash; the component D is selected from one or more of kaolin, pumice and coal gangue.
[0008] Preferably, in the mixture A, the mass ratio of activated carbon, nano-silicon dioxide and nano-aluminum oxide is 1:0.05-0.1:0.05-0.1.
[0009] Preferably, the mass ratio of component C to component D is 1-2:1.
[0010] Preferably, the mass ratio of mixture A to mixture B is 1:2-4.
[0011] Preferably, the average particle size of the activated carbon is 40-60 μm.
[0012] Preferably, the SiO2 content of the nano-silicon dioxide is greater than 99%, and the average particle size is 30-40nm.
[0013] Preferably, the Al2O3 content of the nano-alumina is greater than 99%, and the average particle size is 10-30nm.
[0014] Preferably, the average particle size of component C is 10-20 μm.
[0015] Preferably, the average particle size of component D is 20-40 μm.
[0016] A second aspect of the present invention provides a method for preparing an anti-corrosion material for cement slurry, the preparation method comprising:
[0017] Mixing activated carbon, nano silicon dioxide and nano aluminum oxide to obtain a mixture A;
[0018] Mixing component C and component D to obtain a mixture B; wherein the component C is selected from diatomaceous earth and / or fly ash; and the component D is selected from one or more of metakaolin, pumice and coal gangue;
[0019] The mixture A and the mixture B are mixed under a low stirring rate condition and then stirred at a high speed to obtain the anti-corrosion material.
[0020] Preferably, the low stirring rate is 3800-4200 r / min, and the high-speed stirring rate is 11500-12500 r / min.
[0021] The third aspect of the present invention provides the use of the anti-corrosion material described in the first aspect or the anti-corrosion material prepared by the preparation method described in the second aspect in cement slurry, preferably in cement slurry resistant to carbon dioxide corrosion.
[0022] The fourth aspect of the present invention provides a carbon dioxide corrosion resistant cement slurry, which is made of the following raw materials in parts by weight: 100 parts of G-grade oil well cement, 2-6 parts of anti-corrosion material, 2-5 parts of microsilicon, 3-6 parts of reinforcing material, 3-5 parts of expansion toughening material, 1-3 parts of latex powder, 0-2 parts of stabilizer, 0.3-2 parts of dispersant, 2-5 parts of fluid loss reducer, 0.1-2 parts of retarder, 0.2-0.5 parts of defoaming agent and 48-56 parts of water, wherein the anti-corrosion material is the anti-corrosion material described in the first aspect above or the anti-corrosion material prepared by the preparation method described in the second aspect above.
[0023] A fifth aspect of the present invention provides a method for preparing carbon dioxide corrosion resistant cement slurry, the preparation method comprising:
[0024] Mixing the G-class oil well cement with anti-corrosion materials, micro-silicon, reinforcing materials, expansion toughening materials, latex powder, stabilizers and dispersants to obtain a dry mix;
[0025] mixing the fluid loss reducer with a retarder, a defoamer and water to obtain a wet mix;
[0026] The dry mix and the wet mix are mixed to obtain carbon dioxide corrosion resistant cement slurry.
[0027] The sixth aspect of the present invention provides the use of the carbon dioxide corrosion resistant cement slurry described in the fourth aspect or the carbon dioxide corrosion resistant cement slurry prepared by the preparation method described in the fifth aspect in cementing operations of oil and gas wells.
[0028] Preferably, the use temperature of the carbon dioxide corrosion resistant cement slurry is 30-150°C.
[0029] Through the above technical solution, the beneficial technical effects achieved by the present invention are as follows:
[0030] (1) The applicable temperature range of the cement slurry prepared by using the anti-corrosion material for cement slurry provided by the present invention is 30-150°C. The compressive strength of the cement stone after corrosion is greater than 20MPa, and the permeability is less than 0.1mD, or even less than 0.05mD, which significantly improves the anti-CO2 corrosion ability of the cement stone. At the same time, it has no adverse effect on other engineering properties of the cement slurry, and can ensure long-term effective sealing of the cement ring under CCUS corrosion conditions.
[0031] (2) The carbon dioxide corrosion resistant cement slurry of the present invention has good corrosion resistance in a CO2 corrosion environment. Before corrosion, the cement stone has high compressive strength and dense structure. After corrosion, the cement stone has no obvious decline in compressive strength, low permeability, good mechanical properties, good sedimentation stability, good rheological properties and other comprehensive properties. The CO2 corrosion resistant cement slurry system is suitable for temperatures of 30-150°C and below, ensuring the cementing quality of CCUS wells and ensuring the long-term effective sealing performance of the cement ring under CCUS corrosion conditions, thereby realizing efficient CO2 storage. DETAILED DESCRIPTION
[0032] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0033] A first aspect of the present invention provides an anti-corrosion material for cement slurry, the anti-corrosion material comprising a mixture A and a mixture B; wherein the mixture A comprises activated carbon, nano-silicon dioxide and nano-alumina; the mixture B comprises a component C and a component D; the component C is selected from diatomaceous earth and / or fly ash; the component D is selected from one or more of kaolin, pumice and coal gangue.
[0034] In the present invention, the mixture A includes activated carbon, nano silicon dioxide and nano aluminum oxide, and the nano silicon dioxide and nano aluminum oxide are adsorbed in the pores of the activated carbon, and can be slowly released, lasting and repairing. The mixture A mainly works in the later stage.
[0035] In the present invention, after the cement stone contacts with carbon dioxide, the mixture B has a strong volcanic ash activity, takes the lead in the volcanic ash reaction, consumes Ca (OH) 2 in the cement stone, generates dense substances such as hydrated calcium silicate and hydrated calcium aluminate, and adheres to the outside of the cement stone to play a protective role, preventing CO2 from continuing to penetrate the cement stone, that is, a protective film is initially formed outside the cement stone, and as the hydration reaction continues, the hydration products such as hydrated calcium silicate and hydrated calcium aluminate are continuously consumed, and the protective film is destroyed, resulting in signs of damage to the microstructure of the cement stone again. The mixture A slowly releases the nano silicon dioxide and nano alumina therein, plays a filling and plugging role, forms a dense protective film outside the cement stone, and at the same time, the nano silicon dioxide continues to react with the Ca (OH) 2 in the cement stone, preventing the acidic gas from continuing to enter the cement stone, that is, the mixture A can play a role in reinforcing and encrypting the outer cement stone protective film, thereby realizing long-term and effective corrosion protection of the cement stone. The present invention achieves long-term corrosion protection by optimizing the formula of the anti-corrosion material, and the long-term corrosion protection effect is good.
[0036] The invention mixes the mixture A and the mixture B, so the operation is simple and convenient and the feasibility is strong.
[0037] In some embodiments of the present invention, in the mixture A, the mass ratio of activated carbon, nano-silicon dioxide and nano-alumina is 1:0.05-0.1:0.05-0.1.
[0038] In some embodiments of the present invention, the mass ratio of component C to component D is 1-2:1.
[0039] In some embodiments of the present invention, the mass ratio of mixture A to mixture B is 1:2-4.
[0040] The carbon dioxide corrosion-resistant cement slurry made from the above raw materials has good anti-corrosion ability in a CO2 corrosion environment. Before corrosion, the cement stone has high compressive strength and dense structure. After corrosion, the compressive strength of the cement stone has no obvious decline (the strength decline rate is less than 20%), and the permeability is less than 0.1mD, or even less than 0.05mD.
[0041] The cement slurry containing the above anti-corrosion materials has an applicable temperature range of 30-150℃, which can significantly improve the anti-CO2 corrosion ability of cement stone. After corrosion, the compressive strength of cement stone is greater than 20MPa, and the permeability is small. At the same time, it has no adverse effect on other properties of cement stone, and can ensure the long-term effective sealing performance of cement ring under CCUS corrosion conditions.
[0042] In some embodiments of the present invention, the average particle size of the activated carbon is 40-60 μm.
[0043] In some embodiments of the present invention, the SiO2 content of the nano-silicon dioxide is greater than 99%, and the average particle size is 30-40 nm.
[0044] In some embodiments of the present invention, the Al2O3 content of the nano-alumina is greater than 99%, and the average particle size is 10-30 nm.
[0045] In some embodiments of the present invention, the average particle size of component C is 10-20 μm.
[0046] In some embodiments of the present invention, the average particle size of component D is 20-40 μm.
[0047] A second aspect of the present invention provides a method for preparing an anti-corrosion material for cement slurry, the preparation method comprising:
[0048] Mixing activated carbon, nano silicon dioxide and nano aluminum oxide to obtain a mixture A;
[0049] Mixing component C and component D to obtain a mixture B; wherein the component C is selected from diatomaceous earth and / or fly ash; and the component D is selected from one or more of metakaolin, pumice and coal gangue;
[0050] The mixture A and the mixture B are mixed under a low stirring rate condition and then stirred at a high speed to obtain the anti-corrosion material.
[0051] In some embodiments of the present invention, the low stirring rate is 3800-4200 r / min, and the high-speed stirring rate is 11500-12500 r / min.
[0052] In some embodiments of the present invention, in the mixture A, the mass ratio of activated carbon, nano-silicon dioxide and nano-alumina is 1:0.05-0.1:0.05-0.1.
[0053] In some embodiments of the present invention, the mass ratio of component C to component D is 1-2:1.
[0054] In some embodiments of the present invention, the mass ratio of mixture A to mixture B is 1:2-4.
[0055] In some embodiments of the present invention, the activated carbon has a particle size of 40-60 μm.
[0056] In some embodiments of the present invention, the SiO2 content of the nano-silicon dioxide is greater than 99%, and the average particle size is 30-40 nm.
[0057] In some embodiments of the present invention, the Al2O3 content of the nano-alumina is greater than 99%, and the average particle size is 10-30 nm.
[0058] In some embodiments of the present invention, the average particle size of component C is 10-20 μm.
[0059] In some embodiments of the present invention, the average particle size of component D is 20-40 μm.
[0060] The third aspect of the present invention provides the use of the anti-corrosion material described in the first aspect or the anti-corrosion material prepared by the preparation method described in the second aspect in cement slurry, preferably in cement slurry resistant to carbon dioxide corrosion.
[0061] The anti-corrosion material of the present invention is used to prepare carbon dioxide corrosion resistant cement slurry, which can be implemented simply and conveniently. After the cement stone contacts carbon dioxide, the mixture B undergoes a volcanic ash reaction, consumes Ca(OH)2 in the cement stone, produces hydrated calcium silicate, hydrated calcium aluminate and other substances, protects the cement stone from carbon dioxide corrosion, and initially forms a protective film. As the hydration reaction continues, the hydration product is continuously consumed, resulting in signs of damage to the cement stone microstructure. At this time, the mixture A slowly releases the nano silicon dioxide and nano aluminum oxide therein, plays a filling and plugging role, forms a dense protective film outside the cement stone, and the nano silicon dioxide and Ca(OH)2 in the cement stone continue to react, preventing acidic gas from continuing to enter the cement stone. Therefore, the prepared cement slurry can play a role in lasting carbon dioxide corrosion resistance.
[0062] The fourth aspect of the present invention provides a carbon dioxide corrosion resistant cement slurry, which is made of the following raw materials in parts by weight: 100 parts of G-grade oil well cement, 2-6 parts of anti-corrosion material, 2-5 parts of microsilicon, 3-6 parts of reinforcing material, 3-5 parts of expansion toughening material, 1-3 parts of latex powder, 0-2 parts of stabilizer, 0.3-2 parts of dispersant, 2-5 parts of fluid loss reducer, 0.1-2 parts of retarder, 0.2-0.5 parts of defoaming agent and 48-56 parts of water, wherein the anti-corrosion material is the anti-corrosion material described in the first aspect above or the anti-corrosion material prepared by the preparation method described in the second aspect above.
[0063] In the present invention, the carbon dioxide corrosion-resistant cement slurry prepared by the above raw materials has good corrosion resistance in a CO2 corrosion environment. The cement stone has high compressive strength and dense structure before corrosion. After corrosion, the compressive strength of the cement stone does not decline significantly, the permeability is small, and the mechanical properties are good. At the same time, the comprehensive properties such as sedimentation stability and rheology are good. It can be used in a CO2 corrosion-resistant cement slurry system with a temperature of 30-150°C and below, to ensure the cementing quality of CCUS wells and realize efficient CO2 storage.
[0064] In some embodiments of the present invention, the SiO2 content of the micro-silicon is not less than 90%, the average particle size is 5-10 μm, and the 45 μm sieve residue is ≤5%.
[0065] In the present invention, the reinforcing material is selected from reinforcing materials for cementing oil well cement.
[0066] In some embodiments of the present invention, the reinforcing material is selected from inorganic mineral powder materials, preferably mineral powder DRB-1S produced by China National Petroleum Corporation Engineering Technology Research Institute Co., Ltd.
[0067] In the present invention, the expansion toughening material is selected from the expansion toughening material for cementing oil well cement.
[0068] In some embodiments of the present invention, the expansion toughening material is selected from rubber materials, preferably rubber DRE-3S.
[0069] In the present invention, the latex powder is selected from latex powder for cementing oil well cement.
[0070] In some embodiments of the present invention, the latex powder is selected from polymers, preferably polymer DRT-1S.
[0071] In the present invention, the stabilizer is selected from stabilizers for cementing oil well cement.
[0072] In some embodiments of the present invention, the stabilizer is selected from attapulgite materials, preferably ore powder DRK-2S.
[0073] In some embodiments of the present invention, the dispersant is selected from polystyrene sulfonate compounds and / or condensation products of formaldehyde and acetone.
[0074] In some embodiments of the present invention, the fluid loss agent is selected from polyacrylamide compounds.
[0075] In some embodiments of the present invention, the retarder is selected from acrylamide compounds.
[0076] In some embodiments of the present invention, the defoaming agent is selected from one or more of tributyl phosphate, polyoxypropylene glycerol and polydimethylsiloxane.
[0077] A fifth aspect of the present invention provides a method for preparing carbon dioxide corrosion resistant cement slurry, the preparation method comprising:
[0078] Mixing the G-class oil well cement with anti-corrosion materials, micro-silicon, reinforcing materials, expansion toughening materials, latex powder, stabilizers and dispersants to obtain a dry mix;
[0079] mixing the fluid loss reducer with a retarder, a defoamer and water to obtain a wet mix;
[0080] The dry mix and the wet mix are mixed to obtain carbon dioxide corrosion resistant cement slurry.
[0081] The above-mentioned G-grade oil well cement, anti-corrosion material, microsilicon, reinforcing material, expansion toughening material, latex powder, stabilizer, dispersant, fluid loss reducer, retarder and defoaming agent are the same as those in the fourth aspect. Please refer to the previous description for details and will not be repeated here.
[0082] The sixth aspect of the present invention provides the use of the carbon dioxide corrosion resistant cement slurry described in the fourth aspect or the carbon dioxide corrosion resistant cement slurry prepared by the preparation method described in the fifth aspect in cementing operations of oil and gas wells.
[0083] In some embodiments of the present invention, the use temperature of the carbon dioxide corrosion resistant cement slurry is 30-150°C.
[0084] According to a particularly preferred embodiment of the present invention, the method for preparing carbon dioxide corrosion resistant cement slurry specifically comprises the following steps:
[0085] (1) Preparation of anti-corrosion material: Activated carbon, nano-silicon dioxide and nano-alumina are mixed uniformly in a mass ratio of 1:0.05-0.1:0.05-0.1 to obtain a mixture A; at least one of diatomaceous earth and fly ash is mixed uniformly with at least one of metakaolin, pumice and coal gangue in a mass ratio of 1-2:1 to obtain a mixture B; the mixture A and the mixture B are mixed uniformly in a mass ratio of 1:2-4 to obtain an anti-corrosion material;
[0086] (2) Weighing oil well cement, anti-corrosion material, microsilicon, reinforcing material, expansion toughening material, latex powder, stabilizer and dispersant according to the formula amount, and evenly blending to obtain a dry mix; weighing fluid loss reducer, retarder and defoamer according to the formula amount, and stirring evenly to obtain a wet mix; pouring the dry mix evenly into the wet mix at a speed of 4000±200r / min, and after the dry mix is completely added to the wet mix, covering the mixing cup with a lid, adjusting the stirrer speed to 12000±500r / min, and continuing stirring for 30-40s, preferably 35s, to obtain a carbon dioxide corrosion resistant cement slurry.
[0087] The present invention will be described in detail below through examples.
[0088] In the following examples and comparative examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if no manufacturer is specified, are all conventional products that can be obtained through commercial channels.
[0089] G-grade oil well cement is high sulfate resistance (HSR) G-grade oil well cement, produced by Dalian Cement Group Co., Ltd.
[0090] Microsilicon: Its SiO2 content is 95%, the average particle size is 8μm, and the 45μm sieve residue is 4.2%.
[0091] The reinforcing material is DRB-1S, a reinforcing material ore powder for oil well cementing, produced by China National Petroleum Corporation Engineering Technology Research Institute Co., Ltd.
[0092] The expansion toughening material is DRE-3S, a toughening material rubber for oil well cementing, produced by China National Petroleum Corporation Engineering Technology Research Institute Co., Ltd.
[0093] The latex powder is latex powder polymer DRT-1S for oil well cementing, produced by China National Petroleum Corporation Engineering Technology Research Institute Co., Ltd.
[0094] The stabilizer is high temperature stabilizer ore powder DRK-2S for cementing oil well cement, produced by China National Petroleum Corporation Engineering Technology Research Institute Co., Ltd.
[0095] The dispersant is an aldehyde-ketone polycondensate type DRS-1S for oil well cementing, produced by China National Petroleum Corporation Engineering Technology Research Institute Co., Ltd.
[0096] The fluid loss reducer is acrylamide type DRF-1S for cementing oil well cement, produced by China National Petroleum Corporation Engineering Technology Research Institute Co., Ltd.
[0097] The retarder is an organic acid retarder DRH-1L for oil well cementing, produced by China National Petroleum Corporation Engineering Technology Research Institute Co., Ltd.
[0098] The defoaming agent is an organic ester defoaming agent DRX-1L for oil well cementing, produced by China National Petroleum Corporation Engineering Technology Research Institute Co., Ltd.
[0099] According to the national standard GB / T 19139-2012 "Test Methods for Oil Well Cement", the experiment was carried out to evaluate the conventional engineering properties (density, fluidity, API water loss) of the cement slurry system as well as the compressive strength and permeability before and after corrosion. The main experimental instruments are: 30-60 type tile edge mixer; TG7370D type booster curing kettle, Shenyang Tiger Petroleum Instrument and Equipment Manufacturing Co., Ltd.; HH-420 type constant temperature digital display water tank, Changzhou Yineng Experimental Instrument Factory; YAW-300B hydraulic pressure testing machine, Jinan Xinshijin Testing Machine Co., Ltd.; CO2 corrosion environment simulation system, a product of China National Petroleum Corporation Engineering Technology Research Institute Co., Ltd.
[0100] Fluidity: Tested in accordance with national standard GB / T 19139-2012 "Test methods for oil well cement".
[0101] API water loss: Tested in accordance with the national standard GB / T 19139-2012 "Test methods for oil well cement".
[0102] Cement stone corrosion is cured by using the "CO2 corrosion environment simulation system" invented by China National Petroleum Corporation Engineering Technology Co., Ltd. or a device capable of pressurized curing in a CO2 gas / liquid environment.
[0103] Compressive strength before and after corrosion: tested in accordance with the national standard GB / T 19139-2012 "Test methods for oil well cement".
[0104] Strength loss rate: Strength loss rate = (T2-T1) / T1, where T1 is the compressive strength of cement paste before corrosion and T2 is the compressive strength of cement paste after corrosion.
[0105] Permeability: Tested in accordance with national standard GB / T 19139-2012 “Test methods for oil well cement”.
[0106] Preparation Example 1
[0107] A method for preparing an anti-corrosion material comprises the following steps:
[0108] (1) Activated carbon, nano-silicon dioxide and nano-alumina are fully mixed and uniformly mixed in a mass ratio of 1:0.05:0.05. The activated carbon is commercially available and has a mesh size of 325. The nano-silicon dioxide is commercially available and has a SiO2 content of 99.5% and an average particle size of 30 nm. The nano-alumina is commercially available and has an average particle size of 30 nm and an Al2O3 content of 99.3%. The three substances are uniformly mixed to obtain a mixture A.
[0109] (2) mixing diatomaceous earth and metakaolin uniformly in a mass ratio of 1:1 to obtain a mixture B;
[0110] (3) The mixture A and the mixture B are uniformly mixed in a mass ratio of 1:2 to obtain an anti-corrosion material.
[0111] Preparation Example 2
[0112] A method for preparing an anti-corrosion material comprises the following steps:
[0113] (1) Activated carbon, nano-silicon dioxide and nano-alumina are fully mixed and uniformly mixed in a mass ratio of 1:0.1:0.1. The nano-silicon dioxide is commercially available and has a SiO2 content of 99.9% and an average particle size of 40 nm. The nano-alumina is commercially available and has an average particle size of 20 nm and an Al2O3 content of 99.9%. The three substances are uniformly mixed to obtain a mixture A.
[0114] (2) mixing fly ash and coal gangue evenly in a mass ratio of 2:1 to obtain a mixture B;
[0115] (3) The mixture A and the mixture B are uniformly mixed in a mass ratio of 1:3 to obtain an anti-corrosion material.
[0116] Preparation Example 3
[0117] A method for preparing an anti-corrosion material comprises the following steps:
[0118] (1) Activated carbon, nano-silicon dioxide and nano-alumina are fully mixed and uniformly mixed in a mass ratio of 1:0.2:0.1. The activated carbon is commercially available and has a mesh size of 325; the nano-silicon dioxide is commercially available and has a SiO2 content of 99.8% and an average particle size of 30 nm; the nano-alumina is commercially available and has an average particle size of 30 nm and an Al2O3 content of 99.5%. The above three substances are uniformly mixed to obtain a mixture A;
[0119] (2) mixing fly ash and pumice evenly in a mass ratio of 3:1 to obtain a mixture B;
[0120] (3) The mixture A and the mixture B are uniformly mixed in a mass ratio of 1:5 to obtain an anti-corrosion material.
[0121] Preparation Comparative Example 1
[0122] The diatomaceous earth and coal gangue are mixed and stirred evenly in a mass ratio of 2:1 to obtain an anti-corrosion material.
[0123] Preparation Comparative Example 2
[0124] (1) Nano-silicon dioxide and nano-alumina are fully mixed and uniformly mixed in a mass ratio of 1:1. The nano-silicon dioxide is commercially available and has a SiO2 content of 99.5% and an average particle size of 30 nm. The nano-alumina is commercially available and has an average particle size of 30 nm and an Al2O3 content of 99.3%. The two substances are uniformly mixed to obtain a mixture A.
[0125] (2) mixing diatomaceous earth and metakaolin uniformly in a mass ratio of 1:1 to obtain a mixture B;
[0126] (3) The mixture A and the mixture B are uniformly mixed in a mass ratio of 1:3 to obtain an anti-corrosion material.
[0127] Example 1
[0128] The cement slurry formula is as follows by weight percentage: 100 parts of G-grade oil well cement, 3 parts of the anti-corrosion material obtained in Preparation Example 1, 3 parts of micro-silicon, 5 parts of reinforcing material, 4 parts of expansion toughening material, 2 parts of latex powder, 1 part of stabilizer, 1 part of dispersant, 3 parts of fluid loss reducer, 0.5 parts of retarder, 0.2 parts of defoamer and 53 parts of water. The cement slurry density is 1.88 g / cm 3 , the experimental results are shown in Table 1.
[0129] Example 2
[0130] The cement slurry formula is as follows by weight percentage: 100 parts of G-grade oil well cement, 3 parts of anti-corrosion material obtained in Preparation Example 2, 3 parts of micro-silicon, 5 parts of reinforcing material, 4 parts of expansion toughening material, 2 parts of latex powder, 1 part of stabilizer, 1 part of dispersant, 3 parts of fluid loss reducer, 0.5 parts of retarder, 0.2 parts of defoamer and 53 parts of water. The cement slurry density is 1.88 g / cm 3 , the experimental results are shown in Table 1.
[0131] Example 3
[0132] Compared with Example 2, different amounts of anti-corrosion materials were added. The cement slurry formula was as follows by weight percentage: 100 parts of G-grade oil well cement, 5 parts of anti-corrosion materials obtained in Preparation Example 2, 3 parts of micro-silicon, 5 parts of reinforcing materials, 4 parts of expansion toughening materials, 2 parts of latex powder, 1 part of stabilizer, 1 part of dispersant, 3 parts of fluid loss additive, 0.5 parts of retarder, 0.2 parts of defoamer and 53 parts of water. The cement slurry density was 1.88 g / cm 3 , the experimental results are shown in Table 1.
[0133] Example 4
[0134] The cement slurry formula is as follows by weight percentage: 100 parts of G-grade oil well cement, 6 parts of the anti-corrosion material obtained in Preparation Example 2, 2 parts of microsilicon, 6 parts of reinforcing material, 3 parts of expansion toughening material, 1 part of latex powder, 2 parts of stabilizer, 2 parts of dispersant, 2 parts of fluid loss reducer, 2 parts of retarder, 0.2 parts of defoamer and 56 parts of water. The cement slurry density is 1.88 g / cm 3 , the experimental results are shown in Table 1.
[0135] Example 5
[0136] The cement slurry formula is as follows by weight percentage: 100 parts of G-grade oil well cement, 2 parts of the anti-corrosion material obtained in Preparation Example 2, 5 parts of micro-silicon, 3 parts of reinforcing material, 6 parts of expansion toughening material, 3 parts of latex powder, 0.4 parts of stabilizer, 1 part of dispersant, 5 parts of fluid loss reducer, 0.1 parts of retarder, 0.2 parts of defoamer and 48 parts of water. The cement slurry density is 1.88 g / cm 3 , the experimental results are shown in Table 1.
[0137] Example 6
[0138] Compared with Example 2, different anti-corrosion materials are added. The cement slurry formula is as follows by weight percentage: 100 parts of G-grade oil well cement, 3 parts of anti-corrosion material obtained in Preparation 3, 3 parts of microsilicon, 5 parts of reinforcing material, 4 parts of expansion toughening material, 2 parts of latex powder, 1 part of stabilizer, 1 part of dispersant, 3 parts of fluid loss reducer, 0.5 parts of retarder, 0.2 parts of defoamer and 53 parts of water. The cement slurry density is 1.88 g / cm 3 , the experimental results are shown in Table 1.
[0139] Comparative Example 1
[0140] Compared with Example 2, different anti-corrosion materials are added. The cement slurry formula is as follows by weight percentage: 100 parts of G-grade oil well cement, 3 parts of anti-corrosion materials obtained in Preparation Comparative Example 1, 3 parts of micro-silicon, 5 parts of reinforcing materials, 4 parts of expansion toughening materials, 2 parts of latex powder, 1 part of stabilizer, 1 part of dispersant, 3 parts of fluid loss reducer, 0.5 parts of retarder, 0.2 parts of defoamer and 53 parts of water. The cement slurry density is 1.88 g / cm 3 , the experimental results are shown in Table 1.
[0141] Comparative Example 2
[0142] Compared with Example 2, different anti-corrosion materials are added. The cement slurry formula is as follows by weight percentage: 100 parts of G-grade oil well cement, 3 parts of anti-corrosion materials obtained in Comparative Example 2, 3 parts of microsilicon, 5 parts of reinforcing materials, 4 parts of expansion toughening materials, 2 parts of latex powder, 1 part of stabilizer, 1 part of dispersant, 3 parts of fluid loss reducer, 0.5 parts of retarder, 0.2 parts of defoamer and 53 parts of water. The cement slurry density is 1.88 g / cm 3 , the experimental results are shown in Table 1.
[0143] Comparative Example 3
[0144] Compared with Example 2, no anti-corrosion material is added. The cement slurry formula is as follows by weight percentage: 100 parts of G-grade oil well cement, 3 parts of microsilicon, 5 parts of reinforcing material, 4 parts of expansion toughening material, 2 parts of latex powder, 1 part of stabilizer, 1 part of dispersant, 3 parts of fluid loss reducer, 0.5 parts of retarder, 0.2 parts of defoamer and 53 parts of water. The cement slurry density is 1.88 g / cm 3 , the experimental results are shown in Table 1.
[0145] Table 1 Experimental results of examples and comparative examples
[0146]
[0147]
[0148] Table 1 Experimental results of embodiments and comparative examples (continued)
[0149]
[0150] From the data in Table 1, it can be seen that the fluidity of all embodiments is greater than 20cm, and the API water loss is less than 50mL, which meets the requirements of cementing construction. The compressive strength of all embodiments after corrosion is greater than 20MPa, the strength loss rate is less than 20%, and the permeability is less than 0.1mD, with good performance, meeting the requirements of cementing sealing.
[0151] From the experimental data of Examples 1-3, it can be seen that, using the cement slurry of Example 1, after 60 days of corrosion, the compressive strength decayed from 32.6MPa to 27.9MPa, the compressive strength after corrosion was greater than 20MPa, and the permeability was less than 0.05mD, the mechanical properties of the cement paste after corrosion were good, and the sealing requirements were met. Within the scope defined by the present invention, adjusting the proportion of each component in the anti-corrosion material and the amount of the anti-corrosion material added had no adverse effects on the density, fluidity, API water loss, etc. of the cement slurry system, and at the same time, the compressive strength of the cement paste after corrosion was greater than 20MPa, the permeability was less than 0.05mD, and the cement paste had good anti-corrosion performance.
[0152] It can be seen from the experimental data of Example 2 and Examples 4 and 5 that after the temperature changes, the amount of different admixtures is adjusted as needed, and the obtained cement slurry system has good engineering performance. At the same time, after curing under corrosive conditions, the compressive strength is greater than 20MPa, the permeability is less than 0.05mD, and the anti-corrosion performance is good. That is, within the range of the amount of each material, it can be adjusted according to different temperatures to meet the use requirements at different temperatures.
[0153] From the data of Example 2 and Comparative Examples 1-2, it can be seen that after corrosion, the compressive strength of Comparative Examples 1-2 decreased significantly, both less than 20 MPa, and the permeability increased significantly, even greater than 0.1 mD, and the fluidity of Comparative Example 2 was 17 cm, and the fluidity deteriorated.
[0154] From the data of Comparative Example 4, it can be seen that when no anti-corrosion material is added to the cement slurry, the strength of the cement stone before corrosion is 31.5MPa, but after 60 days of corrosion, the compressive strength declines to 15.6MPa, a decline of 50.48%, and the permeability increases from 0.049mD to 0.203mD. The strength declines significantly and the permeability increases significantly.
[0155] In summary, the cement slurry of the present invention has an applicable temperature range of 30-150°C, the compressive strength of the cement stone after corrosion is greater than 20MPa, and the permeability is less than 0.05mD, which significantly improves the anti-CO2 corrosion ability of the cement stone. At the same time, it has no adverse effect on other engineering properties of the cement slurry, and can ensure long-term effective sealing of the cement ring under CCUS corrosion conditions.
[0156] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. An anti-corrosion material for cement slurry, characterized in that: The anti-corrosion material includes mixture A and mixture B; wherein mixture A includes activated carbon, nano-silicon dioxide and nano-alumina; mixture B includes component C and component D; component C is selected from diatomaceous earth and / or fly ash; and component D is selected from one or more of kaolin, pumice and coal gangue.
2. The anti-corrosion material according to claim 1, wherein: In the mixture A, the mass ratio of activated carbon, nano silicon dioxide and nano aluminum oxide is 1:0.05-0.1:0.05-0.1; And / or, the mass ratio of component C to component D is 1-2:1; And / or, the mass ratio of the mixture A to the mixture B is 1:2-4.
3. The anticorrosion material according to claim 1 or 2, wherein: The average particle size of the activated carbon is 40-60 μm; And / or, the SiO2 content of the nano-silicon dioxide is greater than 99% and the average particle size is 30-40nm; And / or, the Al2O3 content of the nano-alumina is greater than 99%, and the average particle size is 10-30nm; And / or, the average particle size of component C is 10-20 μm; And / or, the average particle size of component D is 20-40 μm.
4. A method for preparing an anti-corrosion material for cement slurry, characterized in that: The preparation method comprises: Mixing activated carbon, nano silicon dioxide and nano aluminum oxide to obtain a mixture A; Mixing component C and component D to obtain a mixture B; wherein the component C is selected from diatomaceous earth and / or fly ash; and the component D is selected from one or more of metakaolin, pumice and coal gangue; Under the condition of low stirring rate, the mixture A and the mixture B are mixed, and then stirred at high speed to obtain the anti-corrosion material; Preferably, the low stirring rate is 3800-4200 r / min, and the high-speed stirring rate is 11500-12500 r / min.
5. The preparation method according to claim 6, wherein In the mixture A, the mass ratio of activated carbon, nano silicon dioxide and nano aluminum oxide is 1:0.05-0.1:0.05-0.1; And / or, the mass ratio of component C to component D is 1-2:1; And / or, the mass ratio of the mixture A to the mixture B is 1:2-4.
6. The preparation method according to claim 4 or 5, wherein: The average particle size of the activated carbon is 40-60 μm; And / or, the SiO2 content of the nano-silicon dioxide is greater than 99% and the average particle size is 30-40nm; And / or, the Al2O3 content of the nano-alumina is greater than 99%, and the average particle size is 10-30nm; And / or, the average particle size of component C is 10-20 μm; And / or, the average particle size of component D is 20-40 μm.
7. Use of the anti-corrosion material described in any one of claims 1 to 3 or the anti-corrosion material prepared by the preparation method described in any one of claims 4 to 6 in cement slurry, preferably in cement slurry resistant to carbon dioxide corrosion.
8. A cement slurry for resisting carbon dioxide corrosion, characterized in that: The cement slurry is made of the following raw materials in parts by weight: 100 parts of G-grade oil well cement, 2-6 parts of anti-corrosion material, 2-5 parts of microsilicon, 3-6 parts of reinforcing material, 3-5 parts of expansion toughening material, 1-3 parts of latex powder, 0-2 parts of stabilizer, 0.3-2 parts of dispersant, 2-5 parts of fluid loss reducer, 0.1-2 parts of retarder, 0.2-0.5 parts of defoaming agent and 48-56 parts of water; wherein the anti-corrosion material is the anti-corrosion material described in any one of claims 1 to 3 or the anti-corrosion material prepared by the preparation method described in any one of claims 4 to 6.
9. The cement slurry according to claim 8, wherein: The SiO2 content of the micro-silicon is not less than 90%, the average particle size is 5-10 μm, and the 45 μm sieve residue is ≤5%.
10. The cement slurry according to claim 8 or 9, wherein: The reinforcing material is selected from inorganic ore powder materials, preferably ore powder DRB-1S; And / or, the expansion toughening material is selected from rubber materials, preferably rubber DRE-3S; And / or, the latex powder is selected from polymers, preferably polymer DRT-1S; And / or, the stabilizer is selected from attapulgite materials, preferably ore powder DRK-2S.
11. The cement slurry according to any one of claims 8 to 10, wherein: The dispersant is selected from polystyrene sulfonate compounds and / or condensation products of formaldehyde and acetone; And / or, the fluid loss reducer is selected from polyacrylamide compounds; And / or, the retarder is selected from acrylamide compounds; And / or, the defoaming agent is selected from one or more of tributyl phosphate, polyoxypropylene glycerol and polydimethylsiloxane.
12. A method for preparing carbon dioxide corrosion resistant cement slurry, characterized in that: The preparation method comprises: Mixing G-grade oil well cement with anti-corrosion material, micro-silicon, reinforcing material, expansion toughening material, latex powder, stabilizer and dispersant to obtain a dry mix; wherein the anti-corrosion material is the anti-corrosion material according to any one of claims 1 to 3 or the anti-corrosion material obtained by the preparation method according to any one of claims 4 to 6; mixing the fluid loss reducer with a retarder, a defoamer and water to obtain a wet mix; The dry mix and the wet mix are mixed to obtain carbon dioxide corrosion resistant cement slurry.
13. Use of the carbon dioxide corrosion resistant cement slurry according to any one of claims 8 to 11 or the carbon dioxide corrosion resistant cement slurry prepared by the preparation method according to claim 12 in cementing operations of oil and gas wells.
14. The use according to claim 13, wherein: The use temperature of the carbon dioxide corrosion resistant cement slurry is 30-150°C.
Citation Information
Patent Citations
Oil-well cement additive against carbon dioxide corrosion as well as preparation method and application thereof
CN102010702A
Carbon dioxide (CO2) corrosion-resistant material of oil well cement
CN102464973A
Cementing compositions and methods for high temperature wells
GB0203729D0
Well Treatment Compositions and Methods Utilizing Nano-Particles
US20100096135A1
Cement compositions and methods of using the same
WO2014039301A1
Cited By
Hydrothermal terrestrial heat composite saltwater slurry system and preparation method thereof
CN120794445A
Corrosion-resistant material for cement slurry, carbon dioxide corrosion resistant cement slurry, preparation method, and use
EP4711347A1
